Perilaku Awak Kapal dalam Upaya Peningkatan Perlindungan Dampak Kerusakan Lingkungan - Rusdiana, I Wayan; Abimanyu, Alin (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Ship has its own peculiarities in its definition as a work area. In addition to being a place of work, the ship is also used as a place for the crew to live and carry out their functions as a mode of transportation. For this reason, this research is a correlational study consisting of two independent variables, namely attitudes to maintain environmental cleanliness and attitudes to support participatory-based environmental activities and the dependent variable is behavior to improve environmental protection and management. the purpose of this research is to find out whether there is a relationship between the attitude of maintaining cleanliness and the attitude of supporting environmental activities on the behavior of increasing environmental protection and management. This research was conducted on 58 respondents, who work as crew members taken by stratified random sampling. Primary data collection using questionnaire techniques and field observations. Data were analyzed using SPSS 26 program with descriptive statistics, correlation test and simple and multiple linear regression. The research instrument uses a Likert scale with four alternative answers. The results of the correlation and regression tests at a significant level of a = 0.05, got three conclusions, namely there was a direct influence between the attitude of maintaining environmental cleanliness and the behavior of increasing environmental protection and management, 2) there was a direct influence on the attitude of supporting participatory-based environmental activities on the behavior of increasing protection and environmental management with a value of 3) the attitude of maintaining environmental cleanliness and the attitude of supporting participatory-based environmental activities simultaneously directly affect the behavior of increasing environmental protection and management. Keywords: Attitude and behavior, environment, correlation